CRC handbook of medicinal spices - Duke, James A (CRC, 2012)
Predicts that spices such as capsicum, cinnamon, garlic, ginger, onion, and turmeric will assume relatively more medicinal importance again, as the economic costs and knowledge of the side-effects of prescription pharmaceuticals increase. This work provides the science behind the folklore of over 60 popular spices